1993
DOI: 10.1002/bbpc.19930971239
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Alkali Traces in Coal Combustion by Excimer Laser Induced Fragmentation Fluorescence

Abstract: Gas phase sodium concentrations were measured in situ in the flue gas of a fluidised bed reactor using the excimer laser induced fragmentation fluorescence (ELIF) technique. Several different coals were investigated for a fixed set of reactor conditions at ∼ 1 bar total pressure. Measured signals were converted to absolute concentrations using a calibration system that monitors alkali compounds under well‐defined conditions. Concentrations ranging from the sub‐ppb region to 25 ppb were obtained. Contrasting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A time-integrated expression relating the functional dependence of the signal upon the laser, instrumental, and spectroscopic parameters has been derived and reported in the literature cited. [2][3][4][5] In the case of NaCl, it can be shown that the signal, S, due to the radiative deactivation of excited sodium atoms, (Na*), depends upon the following param eters:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A time-integrated expression relating the functional dependence of the signal upon the laser, instrumental, and spectroscopic parameters has been derived and reported in the literature cited. [2][3][4][5] In the case of NaCl, it can be shown that the signal, S, due to the radiative deactivation of excited sodium atoms, (Na*), depends upon the following param eters:…”
Section: Resultsmentioning
confidence: 99%
“…The exploitation of laser photofragmentation for the detection of alkali compounds under excimer laser irradiation (mostly at 193 nm) is well known and documented. [2][3][4][5][6] In a thorough investigation of photofragment uorescence as an analytical technique, Oldenborg and Baughcum 2 reported the detection of trace amounts of alkali chlorides with parts per billion by volume (ppbv) sensitivities. Hartinger et al 3 measured sodium concentrations in the ue gas of a uidized bed reactor and investigated several different coals, with sensitivities also in the ppbv range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The PFF technique has been applied in a number of different circumstances, including analysis of the alkali released from coal during combustion and pyrolysis, 2 monitoring the alkali content of a pressurized fluidized bed combustor exhaust, 16 and measuring the concentration of trace elements. 22 The excellent sensitivity of the method has been demonstrated by measurement of sub-ppb concentration levels of alkali compounds in complex combustion atmospheres.…”
Section: Detection Of Gas Phase Alkali Compoundsmentioning
confidence: 99%
“…22 The excellent sensitivity of the method has been demonstrated by measurement of sub-ppb concentration levels of alkali compounds in complex combustion atmospheres. 2,16 In general, the technique exhibits a linear fluorescence response for low concentrations of alkali species. However, under some conditions the response may become nonlinear necessitating the application of calibration curves for accurate concentration measurements.…”
Section: Detection Of Gas Phase Alkali Compoundsmentioning
confidence: 99%